2021
DOI: 10.3390/cancers13112690
|View full text |Cite
|
Sign up to set email alerts
|

Current Implications of microRNAs in Genome Stability and Stress Responses of Ovarian Cancer

Abstract: Genomic alterations and aberrant DNA damage signaling are hallmarks of ovarian cancer (OC), the leading cause of mortality among gynecological cancers worldwide. Owing to the lack of specific symptoms and late-stage diagnosis, survival chances of patients are significantly reduced. Poly (ADP-ribose) polymerase (PARP) inhibitors and replication stress response inhibitors present attractive therapeutic strategies for OC. Recent research has focused on ovarian cancer-associated microRNAs (miRNAs) that play signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 164 publications
(180 reference statements)
0
3
0
Order By: Relevance
“…It is worth mentioning that the functional role of miR-206 and miR-26b in the setting of tumors appears to be inversely related to their endogenous expression levels, as previously highlighted by others. 41,53 Indeed, several reports showed that ovarian cancer features DNA hypermethylation and miRNA levels could be increased by demethylating agents. 26,54 Understanding the mechanisms involved in the regulation of miR-206 levels and the role of estrogenic agents in this process 55 warrants further research.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that the functional role of miR-206 and miR-26b in the setting of tumors appears to be inversely related to their endogenous expression levels, as previously highlighted by others. 41,53 Indeed, several reports showed that ovarian cancer features DNA hypermethylation and miRNA levels could be increased by demethylating agents. 26,54 Understanding the mechanisms involved in the regulation of miR-206 levels and the role of estrogenic agents in this process 55 warrants further research.…”
Section: Discussionmentioning
confidence: 99%
“…1A). Evidences showed that miR-NAs own great potentials in combination cancer therapy [29][30][31]. For example, targeting miR-21 could enhance conventional chemotherapeutic efficacy, together with overcoming drug resistance and cancer recurrence [32].…”
Section: Mir-138-1-3p Expression Was Reduced In Sorafenib-resistant Cells and May Participate In Resistance Developmentmentioning
confidence: 99%
“…miRs can be detected in biological fluids, allowing non-invasive diagnosis to discriminate malignant lesions from benign lesions. Gajek et al [ 11 ] summarize the latest findings on the utility of miRs as potential biomarkers for ovarian cancer diagnosis and prognosis as circulating miR profiles reflect the tumor profiles. Furthermore, by modulating the sensitivity of the cancer cells to chemotherapeutic agents they might serve as promising therapeutic for multidrug-resistance ovarian cancer [ 11 ].…”
mentioning
confidence: 99%